Revision of the 'Candidatus Phytoplasma' species description guidelines. Issue 4 (26th April 2022) - Bertaccini, Assunta; Arocha-Rosete, Yaima; Contaldo, Nicoletta; Duduk, Bojan; Fiore, Nicola; Montano, Helena Guglielmi; Kube, Michael; Kuo, Chih-Horng; Martini, Marta; Oshima, Kenro; Quaglino, Fabio; Schneider, Bernd; et al.
Abstract : The genus ' Candidatus Phytoplasma' was proposed to accommodate cell wall-less bacteria that are molecularly and biochemically incompletely characterized, and colonize plant phloem and insect vector tissues. This provisional classification is highly relevant due to its application in epidemiological and ecological studies, mainly aimed at keeping the severe phytoplasma plant diseases under control worldwide. Given the increasing discovery of molecular diversity within the genus ' Ca . Phytoplasma', the proposed guidelines were revised and clarified to accommodate those ' Ca . Phytoplasma' species strains sharing >98.65 % sequence identity of their full or nearly full 16S rRNA gene sequences, obtained with at least twofold coverage of the sequence, compared with those of the reference strain of such species. Strains sharing <98.65 % sequence identity with the reference strain but >98.65 % with other strain(s) within the same ' Ca . Phytoplasma' species should be considered related strains to that ' Ca . Phytoplasma' species. The guidelines herein, keep the original published reference strains. However, to improve ' Ca . Phytoplasma' species assignment, complementary strains are suggested as an alternative to the reference strains. This will be implemented when only a partial 16S rRNA gene and/or a few other genes have been sequenced, or the strain is no longer available for further molecular characterization. Lists of ' Ca . Phytoplasma' species and alternative reference strains described are reported. For new ' Ca . Phytoplasma' species that will be assigned with identity ≥98.65 % of their 16S rRNA gene sequences, a threshold of 95 % genome-wide average nucleotide identity is suggested. When the whole genome sequences are unavailable, two among conserved housekeeping genes could be used. There are 49 officially published ' Candidatus Phytoplasma' species, including ' Ca . P. cocostanzaniae' and ' Ca . P. palmae' described in this manuscript.